Effect of aspirin on all-cause mortality in the healthy elderly - McNeil, J.; Nelson, M.; Woods, R.; Lockery, J.; Wolfe, R.; Reid, Christopher; Kirpach, B.; Shah, R.; Ives, D.; Storey, E.; Ryan, J.; Tonkin, A.; et al. (Massachusetts Medical Society, 2018)
Background: In the primary analysis of the Aspirin in Reducing Events in the Elderly (ASPREE) trial, now published in the Journal, we report that the daily use of aspirin did not provide a benefit with regard to the primary end point of disability-free survival among older adults. A numerically higher rate of the secondary end point of death from any cause was observed with aspirin than with placebo. Methods: From 2010 through 2014, we enrolled community-dwelling persons in Australia and the United States who were 70 years of age or older (or =65 years of age among blacks and Hispanics in the United States) and did not have cardiovascular disease, dementia, or disability. Participants were randomly assigned to receive 100 mg of enteric-coated aspirin or placebo. Deaths were classified according to the underlying cause by adjudicators who were unaware of trial-group assignments. Hazard ratios were calculated to compare mortality between the aspirin group and the placebo group, and post hoc exploratory analyses of specific causes of death were performed. Results: Of the 19,114 persons who were enrolled, 9525 were assigned to receive aspirin and 9589 to receive placebo. A total of 1052 deaths occurred during a median of 4.7 years of follow-up. The risk of death from any cause was 12.7 events per 1000 person-years in the aspirin group and 11.1 events per 1000 person-years in the placebo group (hazard ratio, 1.14; 95% confidence interval [CI], 1.01 to 1.29). Cancer was the major contributor to the higher mortality in the aspirin group, accounting for 1.6 excess deaths per 1000 person-years. Cancer-related death occurred in 3.1% of the participants in the aspirin group and in 2.3% of those in the placebo group (hazard ratio, 1.31; 95% CI, 1.10 to 1.56). Conclusions: Higher all-cause mortality was observed among apparently healthy older adults who received daily aspirin than among those who received placebo and was attributed primarily to cancer-related death. In the context of previous studies, this result was unexpected and should be interpreted with caution.